Tuberculous Osteomyelitis of Orbit- A Case Report - Chakraborti, Chandana; Choudhury, Krittika Pal; Das, Jayanta (Nepalese Journal of Ophthalmology, 2017)
Background: Orbital tuberculosis is a rare manifestation of extrapulmonary tuberculosis. We report an interesting case of osteomyelitis of orbital bone in an Indian child. Case Report: A 9- year old girl presented with a gradually increasing painless swelling of left upper lid and blepharoptosis along with swelling of left side of forehead for last two months. The swelling was soft, fluctuating and non-tender. Diagnostic tap revealed thick pus which prompted us to do an incisional drainage of the abscess. The pus was sterile on microbiological examination. A diagnosis of osteomyelitis of orbit along with cold abscess of infratemporal fossa was made on the basis of clinical examination, positive Mantoux (MX) test, high erythrocyte sedimentation rate (ESR) and bony erosion of frontal and zygomatic bones in contrast enhanced computerized tomography (CECT). Patient showed marked improvement with antitubercular drug (ATD) but a sinus developed at the incision site. Six months later patient presented with occasional serous discharge from the sinus.The patient underwent excision of the sinus along with curettage and debridement of the left frontal bone and the tissue was sent for histopathological and microbiological examination. ATD was continued for 15 months. Her post-treatment three year follow up was without any recurrence. Conclusion: High index of suspicion should be kept for early diagnosis and timely treatment of the orbital tuberculosis. We want to report the case because of its rarity and clinical interest.